George Eliot - Dolin, Tim, 1959- (Oxford world's classics (Oxford University Press). Authors in context., 2005)
In a landmark essay, Virginia Woolf rescued George Eliot from almost four decades of indifference and scorn when she wrote of the 'searching power and reflective richness' of Eliot's fiction. Novels such as Middlemarch and The Mill on the Floss reflect Eliot's complex and sometimes contradictory ideas about society, the artist, the role of women, and the interplay of science and religion. In this book Tim Dolin examines Eliot's life and work and the social and intellectual contexts in which they developed. He also explores the variety of ways in which 'George Eliot' has been recontextualized for modern readers, tourists, cinema-goers, and television viewers. The book includes a chronology of Eliot's life and times, suggestions for further reading, websites, illustrations, and a comprehensive index.